Organic and inorganic fertilizers influence biomass production and esculin content in Cichorium intybus L. - Ali, Zahid; Ganie, Showkat Hussain; Narula, Alka; Abdin, Malik Zainul; Srivastava, Prem Shankar (Journal of Phytology, 2013)
Cichorium intybus L. is a promising and potent industrial medicinal herb but the relatively low content of esculin and unavailability of mass scale propagation protocol are major impediments for the commercial production of the drug. The enhancement in the yield of esculin is hence, highly desirable, which can be achieved by adequate and judicious supply of plants nutrients or by adopting more expensive and complex protocol of biotechnology. The field experiment was designed in random plots to study the effect of organic manure (20 tonnes ha-1) and chemical fertilizers (N240, P120, K100, S80, kg ha−1; Nitrogen, Phosphorus, Potassium and Sulphur, respectively) on the accumulation of esculin and biomass in various plant parts through the various developmental stages, rosette, bolting, pre-flowering, flowering and post-flowering of C. intybus. Esculin yield from dried leaves increased significantly at flowering stage in the plants treated with N80+100+60 + P120 + K100 + S 20+40+20 (31.71% and 111.22 %) when compared with control. Yield of dry leaf biomass ranged between 628.15 to 986.07 kg ha−1 at flowering stage in various treatments.